PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP TINGKATUNDERPRICING IPO (Studi Empiris Pada Perusahaan yang IPO di Bursa Efek Indonesia Tahun 2009- 2014) - Auliya, Reza; Januarti, Indira (Diponegoro Journal of Accounting, 2015)
The purpose of this research is to examine the impact of corporate governance mechanism to level of IPO underpricing. This study used secondary data taken from financial and annually reports one year before company IPO in Indonesia Stock Exchange for years 2009-2014. This study used judgement sampling method. Research population comprise all companies that IPO for the period 2009-2014. A Total sample of 105 companies was used in analysis from total population 138 companies. Hypotheses in this study indicate that board of commissioner size, proportion of commissioner independence, board of director size, committee audit size, institutional ownership, and managerial ownership partially affect the level of underpricing. This study used linier multiple regression analysis for hypotheses testing. Results of this study showed that the proportion of commissioner independence and committee audit size positively affected the level of underpricing. Board of director had a negative effect on the level of underpricing. This study, did not find significant effects of board of commissioner size, institutional ownership and managerial ownership on the level of IPO underpricing.